Extension of SDG Interface Ontology with the indicators of the CGIAR Strategic Research Framework - CGIAR Platform for Big Data in Agriculture (2019)
SDG Interface Ontology integrates the concepts used by the CGIAR Research Framework and the processus described by the SRF